DINAMIKA KOMUNIKASI DALAM PENYELESAIAN KONFLIK PADA PASANGAN DENGAN GAYA ATTACHMENT ANXIOUS DAN AVOIDANT - Dinda Dzakiyyah Nafiisah; Lintang Ratri Rahmiaji (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2026)
This study aims to examine romantic relationship issues and communication patterns in conflict resolution among couples with anxious and avoidant attachment styles. This research employed a qualitative descriptive method involving eight participants, consisting of four individuals with anxious attachment tendencies and four individuals with avoidant attachment tendencies. Data were collected through in-depth interviews and documentation and analyzed using the Miles and Huberman model. The findings reveal that individuals with anxious attachment tendencies are generally more open in expressing their feelings, actively seek reassurance, and attempt to resolve conflicts immediately. In contrast, individuals with avoidant attachment tendencies tend to avoid conflict, require time to regulate their emotions, and are more reserved in expressing their feelings. In the conflict resolution process, anxious individuals are more likely to initiate communication and relationship repair efforts, while avoidant individuals tend to create distance before re-engaging in communication. The study also shows that couples with anxious and avoidant attachment styles maintain a two-way communication pattern, although the communication process is not always balanced.